Influência da intensidade de luz no controle químico de plantas daninhas - Guilherme Augusto de Paiva Ferreira (2021)
In response to low light availability in shading, weeds undergo morphological and physiological changes that can alter their sensitivity to glyphosate and carfentrazone-ethyl herbicides. The objective of this work was to evaluate the influence of light availability on the sensitivity of Merremia cissoides and Euphorbia heterophylla to glyphosate and Digitaria insularis to glyphosate and carfentrazone-ethyl, applied alone and in mixture. Shading increased the quantum yield of photosystem II (ΦPSII) and reduced the electron transport rate (ETR) of M. cissoides, E. heterophylla and D. insularis. Shading also increased the average leaf area of E. heterophylla and reduced the photosynthetic rate (Pn), stomatal conductance (gs) and transpiration (E) of D. insularis. The glyphosate application caused reductions in the ΦPSII and ETR of M. cissoides, E. heterophylla, and D. insularis, in the dry weight of M. cissoides, in the fresh weight of E. heterophylla and the Pn, gs, E, and fresh weight of D. insularis. The dry weight and ETR of M. cissoides and the fresh weight, ΦPSII, and ETR of E. heterophylla showed a high negative correlation with the control. Shading increased the sensitivity of M. cissoides, E. heterophylla, and D. insularis to glyphosate. The recommended dose for the control of M. cissoides at 30 days after sowing (DAS) in shading was 270 g ha-1 of glyphosate, and in full sunlight, 540 g ha-1 of glyphosate. At 73 DAS, the recommended dose for its shading control was 750 g ha-1 of glyphosate. At this stage, in full sunlight, none of the applied doses were efficient in the control. Shading promoted a reduction of 50 and 40% in the M. cissoids control doses compared to full sunlight, at 30 and 73 DAS, respectively. The application at 73 DAS increased the tolerance of M. cissoides to glyphosate by 177.77 and 131.48% in shading and full sunlight, respectively. For E. heterophylla grown in the shade, the dose of 1110 g ha-1 of glyphosate was efficient, with a control greater than 90%. However, in full sunlight, the highest doses tested achieved control levels around 75%, considered unsatisfactory. In shading, the recommended dose for E. heterophylla control is 40% lower than that required in full sunlight and 50% lower than the dose recommended by the manufacturer. For D. insularis grown in shading, the application of glyphosate alone at a dose of 1920 g ha-1 and in a mixture with carfentrazone-ethyl at doses 1536 + 8 and 1152 + 16 g ha-1 was efficient in its control. In the 63% shading environment, the dose of 768 + 24 g ha-1 was also efficient in controlling this species. In full sunlight, none of the doses were effective for D. insularis control, requiring higher doses for managing this species in open environments. Carfentrazone-ethyl applied alone was not efficient in D. insularis control regardless of the culture environment and seemed not to influence the mixture in the control of this species. The light intensity in the cultivation environments needs to be considered in the glyphosate recommendations in the control of M. cissoides, E. heterophylla, and D. insularis as an economically and environmentally adequate practice in the integrated management of these species.